Investigating the influence of colour, weight, and fragrance intensity on the perception of liquid bath soap: An experimental study - Gatti, E; Bordegoni, M; Spence, C (2014)
We report a preliminary experiment designed to investigate people's product expectations (for a liquid soap) as a function of its fragrance and packaging. To this end, a series of soap bottles was produced that were identical in shape but had different intensities of colouring (white, pink, or red). The weight of the bottles also varied (either light -350. g, or heavy -450. g). Two different concentrations of perfume were added to the liquid soap contained in the bottles (either low or high). The participants evaluated the perceived intensity of the fragrance contained in each bottle, the perceived weight of each bottle, and the expected efficacy of the soap itself (that is, the soap's expected "cleaning ability"). The results revealed a significant main effect of the colour of the packaging on the perceived intensity of the soap's fragrance. Significant effects of the perceived weight of the container on both the perceived intensity of the fragrance and on the expected efficacy of the soap were also documented. These results are discussed in terms of the design of multisensory packaging and containers for liquid body soap and, more generally, for body care and beauty products. © 2013 Elsevier Ltd.